Three-dimensional variation propagation modeling for multistage turning process of rotary workpieces. (April 2015) - Du, Shichang; Yao, Xufeng; Huang, Delin; Wang, Meng
Highlights: A variation propagation model of multistage turning processes is developed. Explicit three-dimensional datum error and fixture error expressions are derived. The effectiveness of the model is validated by an example of valve shell. Abstract: In spite of the success of state space modeling approach to describe variation propagation for multistage milling processes (MMPs), the current models cannot be directly applied into variation propagation analysis for multistage turning processes (MTPs) due to the differences of the locating datum schemes. MTPs are widely adopted in manufacturing industry for fabricating rotary workpieces. In this paper, a generic framework for three-dimensional variation propagation modeling for MTPs of rotary workpieces based on differential motion vectors (DMVs) is developed. The explicit three-dimensional datum error and fixture error expressions are derived. By a series of homogeneous transformations of different error sources, a three-dimensional variation propagation model for MTPs is built, in which the datum error, fixture error and so on are described and transmitted in six degrees of freedom. The effectiveness of the proposed model is validated by an example of MTPs of valve shell.